Particle processing by dense gas antisolvent precipitation: ARISE scale-up - Foster, Neil; Kurniawansyah, F.; Tandya, A.; Delgado, C.; Mammucari, R. (Elsevier BV, 2017)
© 2016 Elsevier B.V. The scale-up of an antisolvent particle micronization process was investigated. The atomized rapid injection solvent extraction (ARISE) system utilizes high pressure carbon dioxide as the antisolvent for the precipitation of solutes from organic solutions. The process typically enables the production of dry powders with beneficial morphologies and enhanced properties such as flow-ability and dissolution rates. Para-coumaric acid (PCA) was selected as the model compound to be processed from acetone based solutions using carbon dioxide at 298 K and 9.5 MPa as the antisolvent. Three scales of operation were tested corresponding to 6- and 15-fold increments in processing capacity. Process outcomes were assessed in terms of product characteristics and product recovery. Upon processing by ARISE, the particle size of PCA was reduced up to 23 times consistently across the different operation scales with process recoveries up to 96%.